2001
DOI: 10.1096/fj.00-0139com
|View full text |Cite
|
Sign up to set email alerts
|

Blood vessel maturation in a 3‐dimensional spheroidal coculture model: direct contact with smooth muscle cells regulates endothelial cell quiescence and abrogates VEGF responsiveness

Abstract: Paracrine interactions between endothelial cells (EC) and mural cells act as critical regulators of vessel wall assembly, vessel maturation and define a plasticity window for vascular remodeling. The present study was aimed at studying blood vessel maturation processes in a novel 3-dimensional spheroidal coculture system of EC and smooth muscle cells (SMC). Coculture spheroids differentiate spontaneously in a calcium-dependent manner to organize into a core of SMC and a surface layer of EC, thus mimicking the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
329
2
4

Year Published

2003
2003
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 335 publications
(352 citation statements)
references
References 34 publications
(57 reference statements)
17
329
2
4
Order By: Relevance
“…Previous findings demonstrate that EC in co-culture with vSMC do not proliferate (8,31). It is therefore somewhat unexpected that vinblastine and paclitaxel have such potent inhibitory effects as they are primarily used as antimitotic drugs in cancer treatment.…”
Section: Dose-response Experimentsmentioning
confidence: 98%
“…Previous findings demonstrate that EC in co-culture with vSMC do not proliferate (8,31). It is therefore somewhat unexpected that vinblastine and paclitaxel have such potent inhibitory effects as they are primarily used as antimitotic drugs in cancer treatment.…”
Section: Dose-response Experimentsmentioning
confidence: 98%
“…3 of 15,34,35 ). Similarly, using PAE/VEGFR2, PAE/VEGFR2/NRP1 and PAE/VEGFR2/NRP2 cell lines expressing similar VEGFR2 levels, the authors showed that both VEGF-A165a and VEGF-A121a substantially enhanced VEGFR2 activation (Y951 and Y1175 phosphorylation) when NRP1 is present (Figure 5 of 15 ).…”
Section: Evidence Supporting Neuropilins Modulating Vegf-a121a-inducementioning
confidence: 99%
“…EC monolayer therefore mimics immature microvessels. 47 Thus, these characteristics make the EC/mpc cocultures a model for interplays at work during muscle regeneration. Therefore, what happens once the steady state is reached and the homeostasis of the muscle recovered?…”
Section: The Ménage à Trois In the Skeletal Muscle Vascular Bedmentioning
confidence: 99%